Strategi Layanan Klasikal Sebagai Usaha Peningkatan Kontrol Emosi Peserta Didik - MILA, MILA FEBRI PRATIWI (Jurnal Psikoedukasia, 2023)
During the pandemic, the face of education in Indonesia changed a lot, the digitalization of the world of education began to develop, online learning from e-learning made students dependent on mobile phones and started to get addicted to online games. Control of students' emotions due to playing online games is carried over to school, students express their emotions when surprised, angry or when happy with slank sentences. To find out whether the classical guidance given by counselors in controlling students' emotions is appropriate, it is necessary to examine the problem regarding Classical Guidance Strategies as an Effort to Improve Student Emotion Control. Data were analyzed qualitatively using the case study method. The results of the research on the classical service strategy on emotional control include 3 of the 4 functions of the classical guidance service, namely: the function of understanding, the function of prevention and the function of alleviation.